2016
DOI: 10.1186/s40643-016-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Palm oil mill effluent as a low-cost substrate for bioflocculant production by Bacillus marisflavi NA8

Abstract: Background: Palm oil mill effluent (POME) generated from the palm oil milling process contains high organic matter from which the molecule of interest for bioconversion such as fermentable sugar can be derived. This study examined the enzymatic hydrolysis of complex celluloses and polysaccharides present in POME with the aim to release the simple sugars as low-cost fermentable feedstock convertible into bioflocculant. Results:The maximum concentration of fermentable sugar produced after 24 h of hydrolysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…The most significant parameter at a low level on the main impact was pH and aluminium sulfate, whereby maintaining the fermentation at acidic pH enhanced the flocculating activity of the metabolite produced. Pu et al [29] and Nurul et al [30] have reported that the flocculating activity was not affected by the inoculum size, which supported our finding.…”
Section: Fig 5 Main Effects Of the Nutritional Components On Floccula...supporting
confidence: 91%
“…The most significant parameter at a low level on the main impact was pH and aluminium sulfate, whereby maintaining the fermentation at acidic pH enhanced the flocculating activity of the metabolite produced. Pu et al [29] and Nurul et al [30] have reported that the flocculating activity was not affected by the inoculum size, which supported our finding.…”
Section: Fig 5 Main Effects Of the Nutritional Components On Floccula...supporting
confidence: 91%
“…4b). Similar results regarding the flocculation activity were reported by Nurul Adela et al [5] when Bacillus marisflavi NA was cultivated in palm oil effluent, producing EPS with a flocculation activity of 80% (Table 1). To our knowledge, the highest EPS flocculation activity reported in literature was of 95.7% for Klebsiella mobilis when cultivated in dairy wastewater [8] (Table 1).…”
Section: Flocculation Activity Of Epssupporting
confidence: 88%
“…Only a few studies on the EPS production using low-cost substrates based on industrial or domestic waste streams can be found in the literature. Recently, Nurul Adela et al [5] used palm oil effluent as carbon source, obtaining a maximum concentration of 6.4 g/L of EPS using Bacillus marisflavi NA8 ( Table 1). The maximum bioflocculant production was achieved at an early stationary phase and the EPS flocculation activity reached 80%.…”
Section: Introductionmentioning
confidence: 99%
“…A calibration curve was then used in obtaining the cell mass. Fermentation efficiency was determined with the aid of equations 4 as recommended by Nurul-Adela et al, (2014)…”
Section: Glucose Fermentation Pre-treatmentmentioning
confidence: 99%